Isolation and Identification of Shigella SonneiProducing Shiga Toxin from Children with Bloody Diarrhea and Evaluation of the Inhibition Effectiveness of Zinc oxide Nanoparticles - Alwan, Hayfaa Rajab; Dahham, Shaymaa Naji; Dhayea, Ahmed Hussein; Maaroof, Mohammed Nadhir (Iraqi Journal of Science, 2024)
Shigella infection strains producing shiga toxin results in bloody diarrheais a dangerous symptom in children under five years of age that can even lead to death. Therefore, this study was conducted to isolate Shigella strains producing shiga toxin from 150 samples which were taken from bloody stool of children under the five years of age. They were suffering from the diarrhea during the period from March 2021 to March 2022 in Tikrit city, Iraq. The results showed the possibility to isolate six isolates of Shigella sonnei at ratio 4% of the total samples. The isolates producing shiga toxin were identified by using stx1 gene. The results showed two isolates of Shigella possessing stx1 gene, at ratio 33.33 of total S. sonnei strains. The two isolates producing shiga toxin have been submitted to NCBI, then accepted as Iraqi strains in NCBI under the registration numbers OK127759.1 and OK127760.1. The Iraqi strains registered in NCBI showed agreement with a global strain of 99-100% that were recorded by registration numbers in Malaysia (CP060117.1), China (CP000038.1), United Kingdom (CP066810.1), Hungary (CP019689.1), Somalia (CP023645.1), Spain (CP022672.1), Italy (CP035008.1), India (CP041322.1), Australia (CP045932.1), Nigeria (CP046286.1), Switzerland (CP049183.1), USA (CP053751.1) and South Korea (CP055292.1). As for the sensitivity test, the results showed that the strain OK127759.1 was resistant to antibiotics azithromycin, ceftazidime, cefotaxime, ceftriaxone, augmentin and tetracycline. And it was sensitive to gentamicin and intermediately sensitive to ampicillin, chloramphenicol and nalidixic acid. As for the strain OK127760.1, the results showed his strain was intermediately sensitive to gentamicin and resistant to the other antibiotics which were used in the test. ZnO-NPs with a concentration of 200 μg/ml showed the highest inhibitory effectiveness against S. sonnei strains OK127759.1 and OK127760.1 with inhibition diameter of 22 mm and 21 mm respectively.